"With Specious Contentions, He Cast Blemishes on His Holy Ones": Abraham ibn Ezra, Maimonides, and Nahmanides in Zecharyah ben Moshe’s Poetic Preface to Offering of Zeal - Lawee, Eric (Hebrew Union College annual, 2023)
In his lone surviving work, a fifteenth-century rationalist from Crete, Zecharyah ben Moshe, defends Abraham ibn Ezra and Maimonides from strictures made against them by their most formidable critic, Nahmanides. The title under which Zecharyah’s tract comes down in some manuscripts, Offering of Zeal (תואנק תחנמ), captures the work’s dual nature: a literary oblation to pillars of medieval Jewish rationalist biblical interpretation that takes the form of zealous criticisms of one whom Zecharyah characterizes as their unworthy, and even unscrupulous, rival. My article explores Zecharyah’s skillfully wrought poetic preface, concentrating on its conceptual components, contextual elements, and depictions of his work’s three dramatis personae. One appendix supplies the poem in the original with English translation; another the colophon to a manuscript of the poem not included in a recent critical edition. Study of Zecharyah’s work yields insights into such larger topics as late medieval Byzantine Hebrew biblical scholarship and the astonishingly under-researched afterlife of Nahmanides’ highly influential commentary on the Torah. Zecharyah’s work may safely be considered the ne plus ultra of anti-Nahmanidean criticism in the annals of Jewish literature.